Influence of Cytokinins on Rhizome Mediated Growth and Morphogenesis of an Endangered Medicinal Orchid Geodorum densiflorum (Lam.) Schltr. (Plant Tissue Culture and Biotechnology, 2020)
Effects of different nutrient media, vitamins and peptone on in vitro asymbiotic seed germination of Geodorum densiflorum (Lam.) Schltr. were studied. In vitro developed rhizomes were used to determine the influence of cytokinins on growth and morphogenesis. Seed germination and survival rate of protocorms were highest in MS medium compared to other basal media. The protocorms raised through seed germination directly proliferated into rhizomes in later phase of growth and development. Nodal portions of rhizomes further exhibited growth through formation of direct and callus mediated protocorm like bodies. In general, three types of rhizome movements were noticed; viz. positively geotropic, negatively geotropic and diagravitropic movements. In the PGR free control and in the presence of NAA alone rhizomes exhibited positively geotropic movements. On the contrary, presence of cytokinin either alone or in combination with NAA exhibited diagravitropic movements. Application of TDZ completely suppressed the positively geotropic movement and enhanced the frequency of negatively geotropic movement of rhizomes followed by shoot bud formation. BAP was most effective cytokinin for large scale rhizome mediated multiplication of Geodorum densiflorum and TDZ could be effectively employed for rapid leafy shoot regeneration.Plant Tissue Cult. & Biotech. 30(1): 65-75, 2020 (June)